Which government policies to create sustainable food systems have the potential to simultaneously address undernutrition, obesity and environmental sustainability? - Celia Burgaz; Iris Van-Dam; Kelly Garton; Boyd A. Swinburn; Gary Sacks; Gershim Asiki; Rafael Claro; Adama Diouf; Ana Paula Bartoletto Martins; Stefanie Vandevijvere (BMC, 2024)
Abstract Introduction A transformation of food systems is urgently needed, given their contribution to three ongoing and interlinked global health pandemics: (1) undernutrition and food insecurity, (2) obesity and non-communicable diseases (NCDs), and (3) climate change and biodiversity loss. As policymakers make decisions that shape food systems, this study aimed to identify and prioritise policies with double- or triple-duty potential to achieve healthier and more environmentally sustainable food systems. Methods This study undertook a 4-step methodological approach, including (i) a compilation of international policy recommendations, (ii) an online survey, (iii) four regional workshops with international experts and (iv) a ranking for prioritisation. Policies were identified and prioritised based on their double- or triple-duty potential, synergies and trade-offs. Using participatory and transdisciplinary approaches, policies were identified to have double- or triple-duty potential if they were deemed effective in tackling two or three of the primary outcomes of interest: (1) undernutrition, (2) obesity/NCDs and (3) environmental degradation. Results The desk review identified 291 recommendations for governments, which were merged and classified into 46 initially proposed policies. Based on the results from the online survey, 61% of those policies were perceived to have double- or triple-duty potential. During the workshops, 4 potential synergies and 31 trade-offs of these policies were identified. The final list of 44 proposed policies for healthier and more environmentally sustainable food systems created was divided into two main policy domains: 'food supply chains' and 'food environments'. The outcome with the most trade-offs identified was 'undernutrition', followed by 'environmental sustainability', and 'obesity/NCDs'. Of the top five expert-ranked food supply chain policies, two were perceived to have triple-duty potential: (a) incentives for crop diversification; (b) support for start-ups, and small- and medium-sized enterprises. For food environments, three of the top five ranked policies had perceived triple-duty potential: (a) affordability of healthier and more sustainable diets; (b) subsidies for healthier and more sustainable foods; (c) restrictions on children's exposure to marketing through all media. Conclusion This study identified and prioritised a comprehensive list of double- and triple-duty government policies for creating healthier and more environmentally sustainable food systems. As some proposed policies may have trade-offs across outcomes, they should be carefully contextualised, designed, implemented and monitored.